Upaya Peningkatan Hasil Belajar Siswa Melalui Metode Pembelajaran Discovery Learning - Annisa; Dewi Sholeha (Indonesian Publication Center, 2021)
Abstract The current low PAI student learning outcomes are due to the tendency of teachers to use conventional one-way learning methods where only information is poured from teacher to student, tends to be monotonous and boring for students. Therefore, it is necessary to apply appropriate learning methods to increase and stimulate the active role of students in learning Islamic Religious Education both individually and in groups. One of these methods is the discovery learning method. Referring to this statement, the researcher is interested in conducting literature study reseacrh to indentify efforts to improve student learning outcomes through discovery learning methods in the subject of Islamic Religious Education. The results of this study indicate that discovery learning methods can be effectively applied in Islamic Education learning activities. This discovery learning method can generate a nuanced learning process in the classroom. Students can contribute actively, critically and analytically so that student learning outcomes in learing Islamic Education can also improve. Abstrak Rendahnya perolehan hasil belajar siswa PAI yang terjadi saat ini dapat dikarenakan kecenderungan guru menggunakan metode pembelajaran konvensional yang bersifat satu arah dimana hanya terjadi penuangan informasi dari guru ke siswa, cenderung monoton dan membosankan bagi siswanya. Oleh karena itu, maka perlu adanya penerapan metode pembelajaran yang tepat untuk meningkatkan dan merangsang peran aktif siwa terhadap pembelajaran Pendidikan Agama Islam baik secara individual maupun kelompok. Salah satu metode tersebut yakni metode discovery learning. Mengacu pada pernyataan tersebut maka peneliti tertarik melakukan penelitian studi literatur untuk mengidentifikasi upaya meningkatkan hasil belajar siswa melalui metode pembelajaran discovery learning pada mata pelajaran Pendidikan Agama Islam. Hasil penelitian ini menunjukkan bahwasannya metode discovery learning dapat secara efektif diterapkan dalam kegiatan pembelajaran PAI. Metode discovery learning ini dapat membangkitkan proses pembelajaran yang bernuansa hidup didalam kelas. Siswa dapat berkontribusi secara aktif, kritis dan analitis sehingga hasil belajar siswa dalam pembelajaaran PAI pun dapat turut meningkat.